Light and high-performance copper nano carbon aluminum composite wire and preparation method thereof

By introducing a nanocarbon buffer layer into the copper-aluminum material, and using pipe-installed drawing technology to prepare copper nanocarbon-aluminum composite wire, solving the problem of insufficient conductivity and mechanical properties of traditional copper-clad aluminum materials, achieving high conductivity, excellent mechanical properties and significant weight reduction effects.

CN119581097APending Publication Date: 2025-03-07INST OF ELECTRICAL ENG CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411836927.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional copper-clad aluminum materials have shortcomings in conductivity and mechanical properties, resulting in limited weight reduction, volume reduction and energy consumption reduction. At the same time, their poor ductility and fatigue resistance are also low, affecting the reliability of components.

Method used

By introducing a nanocarbon buffer layer between copper and aluminum, lightweight, high-performance copper nanocarbon-aluminum composite wire is prepared by pipe-mounted drawing technology. The composite wire is a copper, nanocarbon, and aluminum concentric bimetallic nanocarbon composite structure. The outer layer is copper, the core is aluminum, and the middle spacer is nanocarbon.

Benefits of technology

The high conductivity and excellent mechanical properties of composite wires are achieved, with conductivity ≥80% IACS, tensile strength ≥200 MPa, elongation of 10-25%, and weight reduction of 3.5%-38.5%, improving the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581097A_ABST
    Figure CN119581097A_ABST
Patent Text Reader

Abstract

The invention discloses a light and high-performance copper nano carbon aluminum composite wire and a preparation method thereof, the composite wire is of a copper, nano carbon and aluminum concentric bimetal and nano carbon composite structure, the outer layer is oxygen-free copper, the middle interlayer is nano carbon, the core part is aluminum, and the copper accounts for 45%-95% of the volume fraction of the composite wire. Firstly, an oxygen-free copper pipe and an aluminum bar are cleaned and polished; secondly, a nanometer carbon layer is introduced between the copper layer and the aluminum layer through a proper method, then the aluminum bar is put into a pipe, and after plugs are added, the two ends are welded and sealed; and finally, the light and high-performance copper nano carbon-aluminum composite wire is obtained through the processes of drawing, heat treatment and the like. The copper nano carbon-aluminum composite wire has the characteristics of light weight, high strength and high conductivity, and has a certain elastic characteristic while keeping better conductivity. The light and high-performance copper nano carbon aluminum composite wire has a wide application prospect in the fields of aerospace, power electronics, life appliances and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal composite materials, and in particular relates to a lightweight, high-performance copper nano-carbon aluminum composite wire and a preparation method thereof. Background Art

[0003] Although traditional copper-clad aluminum materials have the advantages of good corrosion resistance, low cost, and light weight, the conductivity and mechanical properties of this conductor are greatly reduced (when the volume ratio of the copper layer is 25%, the conductivity of copper-clad aluminum is about 69.5% IACS). Under the same current carrying capacity and stress field, it is necessary to increase the cross-sectional area to ensure that the comprehensive performance meets the application requirements, which limits the extent of weight reduction, volume reduction, and energy consumption reduction. In addition, ordinary copper-clad aluminum materials have poor ductility, are prone to deformation and fracture under special crimping processes, and have poor fatigue resistance, resulting in low reliability of components. With the rapid development of communication navigation, rail transportation, aerospace and other fields, how to further improve the conductivity of copper-aluminum composite materials is of great significance for reducing power loss and alleviating material temperature rise.

[0004] In view of the above situation, it is necessary and of practical significance to research and develop a composite conductor material that is both lightweight and high-performance. Summary of the invention

[0005] In order to overcome the shortcomings of high density, relative lack of copper resources and high cost of pure copper wires, and at the same time, to solve the technical problems of high resistivity and poor heat dissipation of aluminum conductors, the present invention provides a lightweight, high-performance copper nano-carbon aluminum composite wire and a preparation method thereof. By introducing a nano-carbon buffer layer between copper and aluminum and using a tube drawing technology, a lightweight, high-performance composite conductor is prepared, and the preparation process of the present invention is simple and low-cost.

[0006] In the first aspect, the present invention provides a lightweight, high-performance copper nano-carbon aluminum composite wire, which is a concentric bimetallic nano-carbon composite structure of copper, nano-carbon and aluminum, with an outer layer of copper, a core of aluminum, and a middle spacer of nano-carbon. The volume fraction of copper in the composite wire is 45% to 95%.

[0007] Furthermore, the copper is oxygen-free copper with a purity of 99.999%; and the aluminum is high-purity aluminum with a purity of 99.99%.

[0008] Furthermore, the nanocarbon is carbon nanotubes, graphene, fullerene, carbon quantum dots, graphene oxide and graphene quantum dots, etc.

[0009] In a second aspect, the present invention provides a method for preparing a lightweight, high-performance copper nano-carbon aluminum composite wire, comprising the following steps:

[0010] 1) Grinding and cleaning copper tubes and aluminum rods / aluminum wires;

[0011] 2) Introducing a nanocarbon layer between the copper tube and the aluminum rod / wire;

[0012] 3) Put the aluminum rod / aluminum wire or aluminum / nanocarbon into a copper tube or copper / nanocarbon tube with a diameter matching that of the aluminum rod / aluminum wire, and seal both ends of the tube to obtain a copper nanocarbon aluminum composite rod;

[0013] 4) Drawing the copper nano-carbon aluminum composite rod multiple times to obtain the copper nano-carbon aluminum composite wire;

[0014] 5) The composite wire is subjected to heat treatment to obtain a finished product.

[0015] Preferably, in step 2), the method of introducing nanocarbon between the copper tube and the aluminum rod includes but is not limited to: ① growing graphene on the surface of the copper tube by CVD, ② electrodepositing nanocarbon or copper / nanocarbon composite materials on the surface of the aluminum wire / inner surface of the copper tube by pulse electrodeposition, ③ coating nanocarbon on the surface of the aluminum wire / inner surface of the copper tube by coating, wherein the thickness of the nanocarbon or copper / nanocarbon composite materials is less than 1 μm.

[0016] Preferably, in step 2), the copper tube has a length of 120-600 mm and a diameter of 4-20 mm.

[0017] Preferably, in step 2), the diameter of the aluminum wire / aluminum rod as the core is 0.1-0.5 mm smaller than the inner diameter of the copper tube as the outer layer.

[0018] Preferably, in step 4), the composite rod is subjected to multiple drawing processes at a deformation rate of 5%-10% per process. When the diameter is ≥0.5 mm, the composite wire is processed at a rate of 1-10 m per minute; when the diameter is <0.5 mm, the composite wire is processed at a rate of 20-40 m per minute. The composite wire can be processed to a minimum diameter of 0.1 mm.

[0019] Preferably, in step 5), the heat treatment temperature is 150-200°C and the holding time is 0.5-4 h; the heat treatment process is carried out under vacuum conditions or under inert gas protection conditions, and the product is taken out of the furnace after naturally cooling to room temperature.

[0020] Preferably, in the preparation method, the electrical conductivity of the prepared lightweight, high-performance copper nano-carbon aluminum composite wire is ≥80% IACS International Annealed Copper Standard (IACS), the composite wire loses weight by 3.5%-38.5%, has a tensile strength of ≥200 MPa, and an elongation of 10-25%.

[0021] Compared with the prior art, the advantages of the present invention are: the present invention adopts a simple tube-drawing process technology, introduces a nano-carbon layer between copper and aluminum, and reasonably designs the ratio of copper and aluminum, so as to prepare a lightweight, high-performance composite wire. The introduction of nano-carbon can effectively prevent the formation of brittle and poorly conductive intermetallic compounds at the interface while ensuring interface bonding, and reduce the total thickness of the interface layer and the brittle phase Al 2 The formation of Cu improves the bonding and conductivity of the interface. Through parameter regulation, the conductivity of the prepared lightweight, high-performance copper nano-carbon aluminum composite wire is ≥80% IACS, the weight of the composite wire is reduced by 3.5%-38.5%, the tensile strength is ≥200 MPa, and the elongation is 10-25%. The copper nano-carbon aluminum composite wire prepared by the method of the present invention has the characteristics of light weight and high performance, and has a certain elongation characteristic while maintaining good conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings described herein are used to provide further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute improper limitations on the present application.

[0023] Figure 1 This is a process flow chart of preparing a lightweight, high-performance composite wire according to an embodiment of the present invention;

[0024] Figure 2 This is a photo of a lightweight, high-performance copper nano-carbon aluminum composite wire according to an embodiment of the present invention;

[0025] Figure 3 The density and specific conductivity of the lightweight, high-performance copper nano-carbon aluminum composite wire in Example 3 of the present invention are characterized;

[0026] Figure 4 This is a performance characterization of the tensile strength and elongation of the lightweight, high-performance copper nano-carbon aluminum composite wire in Example 3 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments, and the protection scope of the present invention should include the entire contents of the claims. Through the following embodiments, those skilled in the art can implement the entire contents of the claims of the present invention.

[0028] Example 1

[0029] like Figure 1 The preparation process flow chart of the lightweight, high-performance composite wire of the embodiment of the present invention is shown in the structure and composition of the composite wire used in this embodiment. See Example 1 in Table 1.

[0030] The specific process route is:

[0031] First, an oxygen-free copper tube with a length of 120 mm, an outer diameter of 4 mm, and an inner diameter of 3 mm and an aluminum wire with a length of 150 mm and a diameter of 2.9 mm were polished and cleaned;

[0032] Secondly, a carbon nanotube solution with a concentration of 0.1 mg / mL was prepared and evenly coated on the surface of the aluminum wire, and the coating thickness was controlled to be less than 1 μm;

[0033] Subsequently, the copper / carbon nanotube / aluminum composite rod obtained above was subjected to multiple drawing processes with a deformation rate of 10% per process. When the diameter of the composite wire is ≥0.5 mm, the composite wire is processed at a rate of 3 m per minute; when the diameter is <0.5 mm, the composite wire is processed at a rate of 25 m per minute, and the composite wire can be processed to a minimum diameter of 0.1 mm.

[0034] Finally, the composite wire was heat treated under high vacuum at 150 °C for 0.5 h and then naturally cooled to room temperature before being taken out of the furnace.

[0035] After the above process, the performance test results of the copper / carbon nanotube / aluminum composite wire are shown in Example 1 in Table 1.

[0036] Example 2

[0037] The structure and composition of the composite wire used are shown in Example 2 in Table 1.

[0038] The specific process route is:

[0039] First, an oxygen-free copper tube with a length of 160 mm, an outer diameter of 6 mm, and an inner diameter of 4.4 mm and an aluminum wire with a length of 200 mm and a diameter of 4.2 mm were polished and cleaned;

[0040] Secondly, a fullerene solution with a concentration of 0.1 mg / mL was prepared and evenly coated on the surface of the aluminum wire, and the coating thickness was controlled to be less than 1 μm;

[0041] Subsequently, the copper / fullerene / aluminum composite rod obtained above was subjected to multiple drawing processes at a deformation rate of 5% per process. When the diameter of the composite wire is ≥0.5 mm, the composite wire is processed at a rate of 1 m per minute; when the diameter is <0.5 mm, the composite wire is processed at a rate of 20 m per minute, and the composite wire can be processed to a minimum diameter of 0.1 mm.

[0042] Finally, the composite wire was heat treated under high vacuum at 150 °C for 2 h and then naturally cooled to room temperature before being taken out of the furnace.

[0043] After the above process, the performance test results of the copper / fullerene / aluminum composite wire are shown in Example 2 in Table 1.

[0044] Example 3

[0045] The structure and composition of the composite wire used are shown in Example 3 in Table 1.

[0046] The specific process route is:

[0047] First, an oxygen-free copper tube with a length of 250 mm, an outer diameter of 6 mm, and an inner diameter of 4 mm and an aluminum wire with a length of 280 mm and a diameter of 3.9 mm were polished and cleaned;

[0048] Secondly, by using CVD technology and adjusting the ratio of methane and hydrogen in the introduced gas, graphene is grown on the inner and outer surfaces of the oxygen-free copper tube, thus obtaining a copper / graphene composite tube, and the growth thickness of the graphene is less than 1 μm.

[0049] Subsequently, the copper / graphene / aluminum composite rod obtained above was subjected to multiple drawing processes with a deformation rate of 8% per process. When the diameter of the composite wire is ≥0.5 mm, the composite wire is processed at a rate of 5 m per minute; when the diameter is <0.5 mm, the composite wire is processed at a rate of 40 m per minute, and the composite wire can be processed to a minimum diameter of 0.1 mm.

[0050] Finally, the composite wire is heat treated under high vacuum at 150 °C for 1 h and then taken out of the furnace after cooling to room temperature. Figure 2 shown.

[0051] After the above process, the performance test results of copper / graphene / aluminum composite wire are shown in Figure 3 , Figure 4 and Example 3 in Table 1. Figure 3 As shown, the density of pure copper wire is 8.96, and the density of the composite wire in this embodiment is 6.37, which is 29% lower. The specific conductivity of pure copper wire is 6.47, and the specific conductivity of the composite wire in this embodiment is 7.97, which is 23% higher. Figure 4 As shown, the tensile strength of the composite wire in this embodiment is 230 MPa and the elongation is 15%.

[0052] Example 4

[0053] The structure and composition of the composite wire used are shown in Example 4 in Table 1.

[0054] The specific process route is:

[0055] First, an oxygen-free copper tube with a length of 600 mm, an outer diameter of 6 mm, and an inner diameter of 3.4 mm and an aluminum wire with a length of 630 mm and a diameter of 3.28 mm were polished and cleaned;

[0056] Secondly, a copper sulfate solution with a carbon nanotube concentration of 0.1 mg / mL was prepared, and the pH value was adjusted between 1 and 2. By adjusting the electrodeposition parameters, the co-deposition of copper / carbon nanotube composite film on the surface of the aluminum wire was achieved, and the thickness of the deposited layer was controlled to be less than 1 μm.

[0057] Subsequently, the copper / carbon nanotube / aluminum composite rod obtained above was subjected to multiple drawing processes with a deformation rate of 8% per process. When the diameter of the composite wire is ≥0.5 mm, the composite wire is processed at a rate of 10 m per minute; when the diameter is <0.5 mm, the composite wire is processed at a rate of 40 m per minute, and the composite wire can be processed to a minimum diameter of 0.1 mm.

[0058] Finally, the composite wire was heat treated under high vacuum at 200 °C for 2 h and then naturally cooled to room temperature before being taken out of the furnace.

[0059] After the above process, the performance test results of the copper / fullerene / aluminum composite wire are shown in Example 4 in Table 1.

[0060] Example 5

[0061] The structure and composition of the composite wire used are shown in Example 5 in Table 1.

[0062] The specific process route is:

[0063] First, an oxygen-free copper tube with a length of 400 mm, an outer diameter of 7 mm, and an inner diameter of 2.8 mm and an aluminum wire with a length of 420 mm and a diameter of 2.7 mm were polished and cleaned;

[0064] Secondly, seal one end of the copper tube, prepare a graphene oxide solution with a concentration of 5 mg / mL, inject the solution into the copper tube and let it stand for 24 hours, then rinse the copper tube with deionized water to rinse away excess graphene oxide, and obtain a copper / reduced graphene oxide composite tube, with a reduced graphene layer thickness of less than 1 μm.

[0065] Subsequently, the copper / reduced graphene oxide / aluminum composite rod obtained above was subjected to multiple drawing processes with a deformation rate of 10% per process. When the diameter of the composite wire is ≥0.5 mm, the composite wire is processed at a rate of 5 m per minute; when the diameter is <0.5 mm, the composite wire is processed at a rate of 30 m per minute, and the composite wire can be processed to a minimum diameter of 0.1 mm.

[0066] Finally, the composite wire was heat treated under high vacuum at 200 °C for 4 h and then naturally cooled to room temperature before being taken out of the furnace.

[0067] After the above process, the performance test results of the copper / fullerene / aluminum composite wire are shown in Example 5 in Table 1.

[0068] Example 6

[0069] The structure and composition of the composite wire used are shown in Example 6 in Table 1.

[0070] The specific process route is:

[0071] First, an oxygen-free copper tube with a length of 300 mm, an outer diameter of 4 mm, and an inner diameter of 1.7 mm and an aluminum wire with a length of 330 mm and a diameter of 1.55 mm were polished and cleaned;

[0072] Secondly, a copper sulfate solution with a graphene quantum dot concentration of 0.1 mg / mL was prepared, and the pH value was adjusted between 1 and 2. By adjusting the electrodeposition parameters, the co-deposition of copper / graphene quantum dot composite film on the surface of the aluminum wire was achieved, and the thickness of the deposited layer was controlled to be less than 1 μm.

[0073] Subsequently, the copper / graphene quantum dot / aluminum composite rod obtained above was subjected to multiple drawing processes with a deformation rate of 7% per process. When the diameter of the composite wire is ≥0.5 mm, the composite wire is processed at a rate of 10 m per minute; when the diameter is <0.5 mm, the composite wire is processed at a rate of 40 m per minute, and the composite wire can be processed to a minimum diameter of 0.1 mm.

[0074] Finally, the composite wire was heat treated under high vacuum at 200 °C for 0.5 h and then naturally cooled to room temperature before being taken out of the furnace.

[0075] After the above process, the performance test results of the copper / fullerene / aluminum composite wire are shown in Example 6 in Table 1.

[0076] Table 1 Performance test results of copper nano-carbon aluminum composite wire

[0077]

[0078] In summary, the copper nano-carbon aluminum composite wire of the present invention has the following beneficial technical effects:

[0079] (1) The composite wire is a concentric bimetallic nanocarbon composite structure of copper, nanocarbon and aluminum, with an outer layer of copper, a core of aluminum, and a middle spacer of nanocarbon. The volume fraction of copper in the composite wire is 45% to 95%.

[0080] (2) The copper in the outer layer is oxygen-free copper with a purity of 99.999%; the aluminum in the core is high-purity aluminum with a purity of 99.99%.

[0081] (3) The intermediate layer nanocarbon includes carbon nanotubes, graphene, fullerene, carbon quantum dots, graphene oxide and graphene quantum dots, etc.

[0082] (4) The thickness of the intermediate layer of nanocarbon or copper / nanocarbon composite material is less than 1 μm.

[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lightweight, high-performance copper nano-carbon aluminum composite wire, characterized by: The composite wire is a concentric bimetallic nanocarbon composite structure of copper, nanocarbon and aluminum, with an outer layer of copper, a core of aluminum, and a middle interlayer of nanocarbon. The volume fraction of copper in the composite wire is 45% to 95%. The copper is oxygen-free copper with a purity of 99.999%; the aluminum is high-purity aluminum with a purity of 99.99%; The nanocarbon is carbon nanotube, graphene, fullerene, carbon quantum dot, graphene oxide or graphene quantum dot.

2. A method for preparing a lightweight, high-performance copper nano-carbon aluminum composite wire, characterized in that: The following steps are involved: 1) Grinding and cleaning copper tubes and aluminum rods / aluminum wires; 2) Introducing a nano-carbon layer between the copper tube and the aluminum rod and wire; 3) Put the aluminum rod / aluminum wire or aluminum / nanocarbon into a copper tube or copper / nanocarbon tube with a diameter matching that of the aluminum rod / aluminum wire, and seal both ends of the tube to obtain a copper nanocarbon aluminum composite rod; 4) Drawing the copper nano-carbon aluminum composite rod multiple times to obtain the copper nano-carbon aluminum composite wire; 5) The composite wire is subjected to heat treatment to obtain a finished product.

3. The method for preparing a lightweight, high-performance copper nano-carbon aluminum composite wire according to claim 2, characterized in that: In the step 2), the method of introducing nanocarbon between the copper tube and the aluminum rod comprises: ① growing graphene on the surface of the copper tube by CVD method, ② electrodepositing nanocarbon or copper / nanocarbon composite material on the surface of the aluminum wire / inner surface of the copper tube by pulse electrodeposition, and ③ coating nanocarbon on the surface of the aluminum wire / inner surface of the copper tube by coating method, wherein the thickness of the nanocarbon or copper / nanocarbon composite material is less than 1 μm.

4. The method for preparing a lightweight, high-performance copper nano-carbon aluminum composite wire according to claim 2, characterized in that: In the step 2), the copper tube has a length of 120-600 mm and a diameter of 4-20 mm.

5. The method for preparing a lightweight, high-performance copper nano-carbon aluminum composite wire according to claim 2, characterized in that: The diameter of the aluminum wire / aluminum rod as the core is 0.1~0.5mm smaller than the inner diameter of the copper tube as the outer layer.

6. A method for preparing a lightweight, high-performance copper nano-carbon aluminum composite wire according to claim 2, characterized in that: In the step 4), the composite rod is subjected to multiple drawing processes at a deformation rate of 5%-10% per process. When the diameter is ≥0.5 mm, the composite wire is processed at a rate of 1-10 m per minute; when the diameter is <0.5 mm, the composite wire is processed at a rate of 20-40 m per minute. The composite wire can be processed to a minimum diameter of 0.1 mm.

7. The method for preparing a lightweight, high-performance copper nano-carbon aluminum composite wire according to claim 2, characterized in that: In the composite wire heat treatment method, the heat treatment temperature is 150-200 ° C, and the holding time is 0.5-4 h; the heat treatment process is carried out under vacuum conditions or under inert gas protection conditions, and the composite wire is naturally cooled to room temperature before being taken out of the furnace.

8. A lightweight, high-performance copper nano-carbon aluminum composite wire according to any one of claims 1 to 7, characterized in that: The electrical conductivity of the composite wire is ≥80% IACS, the tensile strength is ≥200 MPa, and the elongation is 10-25%.

Citation Information

Patent Citations

  • Method for improving interface of copper-aluminum composite material

    CN108231273A

  • Copper-based composite material containing aluminum carbon nanotubes and preparation method of copper-based composite material

    CN117684041A

  • Copper-clad aluminum composite material of graphene modified copper cladding layer and preparation method of copper-clad aluminum composite material

    CN118136304A

  • Light low-resistance composite conductor and preparation method and application thereof

    CN118231021A

  • Light-weighted wire with high conductivity and its manufacturing method

    JP2007157372A

Cited By

  • High-performance copper-aluminum composite bar with large width-to-thickness ratio and preparation method thereof

    CN119993608A